High Adventure - Hillary, Edmund, 1919-2008 (New York E.P. Dutton & Co., 1955)
Personal record of his mountaineering experiences that reached their climax in the conquest of Mt. Everest
Include Illustration, Glossary and Index
Keywords: Asia--Mount Everest -- Travel -- Mountaineering expeditions